Гладиатор: роман / Б. К. Седов - Седов Б. К. (Воровской закон, 2002)
Экземпляры: ФО-3 (201410) / Инвентарный номер: 50334 / Цена: 70.00 / Сис.шифр: Р2 / Авт.знак: С 28 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6